(untitled) (Research, Society and Development, 2020)
This study investigated the development of life skills of 71 adolescents who practice individual sports, with a mean age of 14.54 ± 1.27 years. The instruments used were the Life Skills Scale for Sport (P-LSSS) and a sociodemographic questionnaire. Data analysis was conducted using the Kolmogorov-Smirnov tests, independent t, MANOVA and Pearson correlation (p <0.05). The results showed that the practitioners with the longest duration of practice had a higher score in the dimensions of teamwork (p = .010), goal setting (p = .018), leadership (p = .026) and communication (p =. 006) when compared to practitioners with less practice time. Fight practitioners had a lower time control score (p = .029) compared to athletics and swimming practitioners. There was a positive correlation between practice time and teamwork (r = .28), goal setting (r = .29) and communication (r = .32). It was concluded that the time of practice is associated with the development of life skills in adolescents.